Formação Jaguarão: uma nova unidade vulcânica mesozóica no Rio Grande do Sul - VIEIRA JUNIOR, NELSON; ROISENBERG, ARI (Pesquisas em Geociências, 1987)
This paper presents a new Mesozoic volcanic sequence whose stratotype is located in the city of Jaguarão, Rio Grande do Sul State (Brazil) and we are formally naming it the Jaguarão Formation. The lava flows include glassy dacites and contain abundant xenolithic material of the crystalline basement. The volcanic pile has a maximum thickness of 80 m (average 40m) and an age around 157 Ma (K-Ar, wholerock). Petrogenetic and geotectonic data define this lithostratigraphic unit as a volcanic event that precludes the Serra Geral Formation (Paraná Basin), from being probably related to the rift system of the Lagoa Mirim marginal basin.